Pengajaran Baca Tulis Al-Qur'an dan Aqidah Akhlak Terhadap Santri Madrasah Ibtidaiyah Menara Qur'an Baiturrohman Desa Cangkring Sari Kecamatan Sukodono Kabupaten Sidoarjo - Novianelly Dwi Rizqisyahputri; Mochamad Dimas Eka Saputra; Nelud Darajaatul Aliyah; Muhammad Yusron Maulana El-Yunusi; Mirza Elmy Safira; Eli Masnawati; Masfufah Masfufah (Jurnal Pengabdian Masyarakat Nusantara, 2023)
The students of Madrasah Ibtidaiyah Menara Qur'an Baiturrohman in Cangkring Sari Village, Sukodono District, Sidoarjo Regency face the problem of boredom in the teaching system. In overcoming this problem, a work program was created with the main objective of teaching reading and writing the Qur'an. The method implemented in the implementation of the work program is the ABCD method. The results of this work program show that students are able to more quickly understand the teaching process provided by the KKN team of Sunan Giri University Surabaya. The KKN team implemented teaching in the form of groups, by classifying each volume and Al-Qur'an. As a result, KKN participants can also understand how each student learns, considering that each student has a different learning process. This program succeeded in increasing the effectiveness of teaching and providing a better understanding of the students, as well as providing insight to the participants of the real work study regarding learning at Madrasah Ibtidaiyah Menara Qur'an Baiturrohman.